Propriedades ópticas de pontos quânticos de InAs em nanomembranas semicondutoras - Barbara Luiza Teixeira Rosa (2014)
In this work we study how the optical properties of InAs quantum dots embedded in III-V semiconductor nanomembranes are a_ected by the neighborhood of the two symmetrically located sample surfaces. Photoluminescence measurements show that the creation of the nanomembranes increase the electron-hole recombination probability of the excited states of the quantum dots, relative to the emission prior to the fabrication of the nanomembranes. This behavior is explained considering the depletion layers induced by the surfaces of the nanomembrane.